MicroRNA dysregulation in multiple sclerosis - de Faria Jr., Omar; Moore, Craig; Kennedy, Timothy; Antel, Jack; Bar-Or, Amit; Dhaunchak, Ajit (Frontiers in Genetics, 2013)
Multiple Sclerosis (MS) is a chronic inflammatory disease characterized by central nervous system (CNS) demyelination and axonal degeneration. Although the cause of MS is still unknown, it is widely accepted that novel drug targets need to focus on both decreasing inflammation and promoting CNS repair. In MS and experimental autoimmune encephalomyelitis (EAE) non-coding small microRNAs (miRNAs) are dysregulated in the immune and central nervous systems. Since individual miRNAs are able to downregulate multiple targeted mRNA transcripts, even minor changes in miRNA expression may lead to significant alterations in post-transcriptional gene expression. Herein, we review miRNA signatures reported in CNS tissue and immune cells of MS patients and consider how altered miRNA expression may influence MS pathology.